The effect of Shallot and Coconut Water as Natural Hormones and Rooton as Synthetic Hormone on Rooting of Chrysanthemum (Dendrathema grandiflora) Cutting Stem - Yayuk Aneka Bety (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2012)
The application of synthetic growth hormones for rooting of chrysanthemum stem especially in rural area is expensive, therefore, alternative natural compound should be found to replace the synthetic hormones. The objective of the study was to obtain the natural compound as alternative hormones for rooting of chrysanthemum cutting stem. The experiment was performed in plastic house in Salatiga district, Central Java, located at + 700 m above sea level, during January to February, 2007. The treatments used were two natural compounds, coconut water dan crushed shallot, and one synthetic hormone i.e., Rooton containing 5% Indol buteric acid (IBA), Naphtalene Acetic Acid (NAA) and Indole Acetic Acid (IAA) and aquadest as control. Experiment was arranged in randomized block design with six replications. The variety used was Puspita Nusantara which has yellow flower and spray type. The result of the experiment indicated that application of coconut water, crushed shallot, synthetic hormone increased root number, root length, root weight, and fresh weight of chrysanthemum cutting stem. Both natural compounds, coconut water and crushed shallot were able to promote rooting of chrysanthemum cutting stem effectively as synthetic hormone did.Keywords: Chrysanthemum; Coconut water; Shallot; Indole buteric acid; Rooting cutting